2007
DOI: 10.1677/joe-06-0191
|View full text |Cite
|
Sign up to set email alerts
|

The emerging role of FOXO transcription factors in pancreatic β cells

Abstract: FOXO transcription factors critically control fundamental cellular processes, including metabolism, cell differentiation, cell cycle arrest, DNA repair, and other reactions to cellular stress. FOXO factors sense the balance between stimuli promoting growth and differentiation versus stress stimuli signaling damage. Integrated through the FOXO system, these divergent stimuli decide on cell fate, a choice between proliferation, differentiation, or apoptosis. In pancreatic b cells, most recent evidence highlights… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
110
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(118 citation statements)
references
References 100 publications
(84 reference statements)
6
110
0
2
Order By: Relevance
“…Activation of FOXO1 is necessary for fatty-acid-induced apoptosis in pancreatic beta cells, while the inhibition of FOXO1 can effectively protect islet beta cells from the toxic effects of fatty acids [10,11]. Previously, we used palmitate-treated MIN6 cells as a model of apoptosis, and chromatin immunoprecipitation (ChIP) coupled to a DNA selection and ligation technology to identify 189 genes to which the FOXO1 protein bound [12].…”
Section: Introductionmentioning
confidence: 99%
“…Activation of FOXO1 is necessary for fatty-acid-induced apoptosis in pancreatic beta cells, while the inhibition of FOXO1 can effectively protect islet beta cells from the toxic effects of fatty acids [10,11]. Previously, we used palmitate-treated MIN6 cells as a model of apoptosis, and chromatin immunoprecipitation (ChIP) coupled to a DNA selection and ligation technology to identify 189 genes to which the FOXO1 protein bound [12].…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that small interfering RNA (siRNA)-mediated knockdown of FOXO reverted the loss of β-cat binding to TCF after cellular oxidative stress [90]. The production and function of FOXO proteins in the pancreatic beta cells have been extensively investigated during the past few years [91]. It will be interesting to examine whether insulin and growth Fig.…”
Section: Foxos Compete With Tcfs For the Limited Pool Of β-Catmentioning
confidence: 99%
“…Insulin/growth factors (GFs) help to restore the balance by two means. First, they stimulate the nuclear exclusion of FOXOs via phosphorylation mediated by PKB/serum-and glucocorticoid-inducible kinase (SGK) [81,82,91]. Second, they enhance the nuclear content of β-cat and the binding of β-cat/TCF to the WNT target gene promoters via a yet to be identified PKB-independent mechanism [13] factors control the balance between FOXO-mediated and WNT-mediated gene transcription (see below).…”
Section: Foxos Compete With Tcfs For the Limited Pool Of β-Catmentioning
confidence: 99%
“…Il faut en outre rappeler que l'hyperglycémie chronique a également des effets délétères au niveau pancréatique, en diminuant la survie et en augmentant l'apoptose des cellules β du pancréas. Dans la mesure où FoxO1 joue un rôle central dans les mécanismes de mort cellulaire [7], en particulier dans la cellule β-pancréatique [8], une augmentation de son activité transcriptionnelle par O-glycosylation pourrait aussi expliquer certains effets toxiques du glucose sur la fonction pancréatique (Figure 2). …”
Section: Hyperglycémie Chronique Et O-glycosylation De Foxo1 : Conséqunclassified